2012
DOI: 10.3389/fnins.2012.00033
|View full text |Cite
|
Sign up to set email alerts
|

The Nervous System and Metabolic Dysregulation: Emerging Evidence Converges on Ketogenic Diet Therapy

Abstract: A link between metabolism and brain function is clear. Since ancient times, epileptic seizures were noted as treatable with fasting, and historical observations of the therapeutic benefits of fasting on epilepsy were confirmed nearly 100 years ago. Shortly thereafter a high fat, low-carbohydrate ketogenic diet (KD) debuted as a therapy to reduce seizures. This strict regimen could mimic the metabolic effects of fasting while allowing adequate caloric intake for ongoing energy demands. Today, KD therapy, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 204 publications
3
36
0
Order By: Relevance
“…31,44 Consistent with this prediction, recently we found that feeding with a KD for 3–4 weeks reduced sensitivity to thermal pain in rats. 43 Establishing broader applicability and identifying key mechanisms of the KD in vivo are essential to uncover novel targets for pain relief.…”
Section: Introductionsupporting
confidence: 61%
“…31,44 Consistent with this prediction, recently we found that feeding with a KD for 3–4 weeks reduced sensitivity to thermal pain in rats. 43 Establishing broader applicability and identifying key mechanisms of the KD in vivo are essential to uncover novel targets for pain relief.…”
Section: Introductionsupporting
confidence: 61%
“…hsa04080" (Neuroactive-ligand-receptor interaction pathway) have a maximum number of EP proteins involved in them. These findings support previous studies according to which there exists a therapeutic relationship between brain activity and metabolism to treat neurological disorders (Masino et al, 2009) (Ruskin and Masino, 2012). Although direct correlation of the "path: hsa04080" and epilepsy could not be established, but this pathway has remained as an important source for the development of various therapeutic strategies against various neurological disorders (Kong et al, 2015).…”
Section: Protein Target-human Pathway (Pt-hp) Networksupporting
confidence: 89%
“…23). During the past 50 years, it was established that ketones can constrain neuronal network activity and ketogenic diets can benefit many patients with epilepsy 24 . More recently, it was shown that rats maintained on ADF exhibit resistance to seizure-induced hippocampal damage and associated cognitive impairment 25 and that IF can reduce seizure frequency in children who do not fully respond to a ketogenic diet 26 .…”
Section: Neuronal Adaptations To Imsmentioning
confidence: 99%